Elektrodeposisi Komposit Hidroksiapatit-Kitosan dari Bahan Lokal pada Baja Tahan Karat SS 304 - Sarah Nasma'ul Aulia; R. Henny Mulyani; Djoko Hadi Prajitno (Jurnal Kartika Kimia, 2019)
In this Research to determine the effect of processing time and the difference of the composition of chitosan in Hydroxyapatite (HA) solution to the weight efficiency of the result from the electrodeposition process, it was used 9 samples but only 3 were carried out into characterization testing they’re HA + Chitosan 10% sample (5 hours), HA + Chitosan 20% (1 hour), HA + Chitosan 20% (5 hours), the current density used during the electrodeposition process is 1.8 A / cm3. The process of stirring with an ultrasonic stirrer is important, so that the colloidal powder contained in the electrolyte solution becomes homogeneous. Characterization tests include X-ray Diffraction (XRD) testing, scanning Electron Microscopy (SEM) and Simulated Body Fluid (SBF). The addition of chitosan to HA alloy solutions is very useful to increase the stickiness of the sediment layer on the substrate, because the properties of HA is very fragile when in direct contact with human body fluids its because of the low level of stability. In this study the highest peak on the X-Ray Diffraction pattern was found in the composite HA + Chitosan 20% (1 hour), which is the position 31.91, and for the% weight of calcium (Ca) in the HA + Chitosan sample 20% (1 hour) also the highest among other samples was 27.03%. From the SBF test results, the highest corrosion rate in the HA + Chitosan 10% sample is 1.076 mpy, while for the HA + Chitosan sample 20% is only 0.058 mpy. Keywords: Electrodeposition, Hydroxyapatite, Chitosan, Ultrasonic Stirrer, XRD, SEM-EDS, SBF, Calsium